PERSEPSI MASYARAKAT NELAYAN TERHADAP PENDIDIKAN ANAK DI KENAGARIAN AIR BANGIS KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Yuherma, Rita; Ansofino, Ansofino; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
Principal issue in this thesis is written on Perception and Participation Fishermen Against Child education in Kenagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat. The purpose of this study was to determine the socio-economic situation as well as describe the Fishermen Community Perceptions and Fishermen Against Public Participation in Childrens Education Kenagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat. The study was conducted using Qualitative Research Methods, qualitative iterative model , using data analysis techniques in the acquisition of data obtained from observations, interviews and observations . After analyzing the collected source of data that includes Reduction and Display Data. After the verification and also draw conclusions and writing the results of the analysis in the form of thesis research. The results of this study reveal that :First : Public Perception Fishermen in Kenagarian Air Bangis towards childrens education is very diverse , but basically they are already aware of the importance of education for their children for the future . All that can be seen from the 47 respondents (94% of 50 respondents ) are already aware of the importance of an education. Second : Fishermen Community Participation in Education Against Kenagarian Air Bangis son. Have a pretty good role can be seen from the consciousness of those who always antusiasi provide motivation to always meet the needs of children such as school children or the needs of the average parent has met the educational needs of their children , take the time to help children with homework , ask the childs learning progress to the teacher or homeroom, knowing what subjects learned in school children, attending school committee meetings whenever held by the school, to contribute funds for the construction of educational facilities around the 39 respondents (78% of 50 respondents ) although it has not everything can be done , but at least their participation in their childrens education can already say either. Third : Socio-Economic Condition of Fishermen Society for childrens education in Kenagarian Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat seen from the results that use only income Fishermen boats can still say economic conditions are still low on a day where their income on average Rp. 15,000 - Rp .50.000, in which fishermen use boats compare the average income as a fisherman around Rp.200 ,000 - Rp .500,000 once went overboard